2016
DOI: 10.1097/01.ogx.0000508248.22573.8b
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Chromosome Mosaicism Reveals Lineage-Specific Depletion of Aneuploid Cells and Normal Developmental Potential

Abstract: Most human pre-implantation embryos are mosaics of euploid and aneuploid cells. To determine the fate of aneuploid cells and the developmental potential of mosaic embryos, here we generate a mouse model of chromosome mosaicism. By treating embryos with a spindle assembly checkpoint inhibitor during the four-to eight-cell division, we efficiently generate aneuploid cells, resulting in embryo death during peri-implantation development. Live-embryo imaging and single-cell tracking in chimeric embryos, containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…These observations are consistent with a second model of clonal depletion (Figure 4), whereby aneuploid cells are actively eliminated or fail to propagate effectively within mosaic embryos, mitigating their deleterious impact. A recent study using a mouse model provides empirical support for this hypothesis, demonstrating that mosaic embryos can be rescued by diploid cells if present in sufficient frequency (≥50%) [84]. This experiment also revealed that the fate of aneuploid cells depends on the type of cell affected.…”
Section: Consequences Of Mosaicism For Embryonic Developmentmentioning
confidence: 64%
See 2 more Smart Citations
“…These observations are consistent with a second model of clonal depletion (Figure 4), whereby aneuploid cells are actively eliminated or fail to propagate effectively within mosaic embryos, mitigating their deleterious impact. A recent study using a mouse model provides empirical support for this hypothesis, demonstrating that mosaic embryos can be rescued by diploid cells if present in sufficient frequency (≥50%) [84]. This experiment also revealed that the fate of aneuploid cells depends on the type of cell affected.…”
Section: Consequences Of Mosaicism For Embryonic Developmentmentioning
confidence: 64%
“…This experiment also revealed that the fate of aneuploid cells depends on the type of cell affected. Aneuploidies occurring in the blastocyst were better tolerated—though still deleterious—when isolated to the extraembryonic TE tissue [84]. Mitotic errors affecting the inner cell mass of mouse embryos were more consequential and eliminated by apoptosis prior to implantation [84].…”
Section: Consequences Of Mosaicism For Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that mosaic blastocysts miscarry more often and implant less frequently than an euploid blastocyst but a proportion of mosaic embryos can implant and result in healthy babies . In a chimeric murine model, mosaic embryos have been shown to undergo a “self‐correcting” mechanism if they contain sufficient euploid cells …”
Section: Weaknessesmentioning
confidence: 99%
“…Moreover, some mosaic embryos—which are usually not implanted—can still grow into healthy newborns . Indeed, recent murine studies suggest that mosaic embryos with a significant complement of euploid cells retain full developmental potential . Mosaicism can go undiagnosed because a single TE biopsy is not representative of the karyotypically heterogeneous monolayer or of the ICM.…”
Section: Blastocyst Developmental Potential As Inferred From the Pgs mentioning
confidence: 99%